2019
DOI: 10.3390/app9112383
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Generation System Based on Fractal Geometry for Batik Pattern Design

Abstract: In order to obtain the automatic simulation generation of traditional handmade batik patterns in a computer, this paper proposes the automatic generation method of batik flower patterns based on fractal geometry. Firstly, we analyze the fractal characteristics of batik flowers and design an automatic flower generation algorithm based on a two-dimensional iterated function system (IFS) and a curve function. The algorithm forms a complete flower pattern. Secondly, a nonlinear function is defined and the flower p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Nevertheless, a computer-aided design was not employed in this work to avoid overloading them with too many new things at once. Computer programs were previously proven successful in batik designs [17][18][19][20], but the local batik artisans were not keen to use them. The gradual incorporation of new techniques into traditional craftsmanship is an appropriate way to transform batik into modern fashion without losing its local identity and charm.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a computer-aided design was not employed in this work to avoid overloading them with too many new things at once. Computer programs were previously proven successful in batik designs [17][18][19][20], but the local batik artisans were not keen to use them. The gradual incorporation of new techniques into traditional craftsmanship is an appropriate way to transform batik into modern fashion without losing its local identity and charm.…”
Section: -Discussionmentioning
confidence: 99%
“…In addition to transferring its knowledge to younger generations to ensure its sustainability, new techniques have been proposed to facilitate batik manufacturing processes. Laitupa et al demonstrated the computer-based creation of new batik motifs [17], whereas Tian et al developed automatic batik flower patterns based on fractal geometry [18]. For pattern recognition, neural networks and deep learning have been implemented on batik fabrics [19,20].…”
mentioning
confidence: 99%
“…This command can be abbreviated as FFF-FFF-FF-FF + F-F. The mathematical formula for forming a graph of interest in the Cartesian coordinates for the x and y axes can be written as follows (Tian, Yuan, Hu, & Shi, 2019)::…”
Section: B Methodsmentioning
confidence: 99%
“…Studies on Batik have been previously conducted by numerous researchers, especially in the field of image generation. One of the studies on Batik was conducted by Tian [8], produced Batik automatically by simply entering a few parameters using the fractal geometry method. In 2020, research on Batik was also conducted by Purba Daru Kusuma to produce Madura-style Batik, implemented on the website by utilizing the sine wave model method [9].…”
Section: Introductionmentioning
confidence: 99%